ความคิดเห็นของครู นักเรียนและปัจจัยที่เกี่ยวข้องต่อการดำเนินงานป้องกันสารเสพติดในสถานศึกษาสังกัดสำนักงานการประถมศึกษาจังหวัดสิงห์บุรี - บุษริน เพ็งบุญ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
As remedying students with substances abuse problem is an onerous task with hopelessly trivial chance of success, preventing them from the problem is thus more promising. This cross-sectional descriptive survey aimed at studying teachers and students opinion and its related factors concerning substances abuse prevention in schools under Singburi Provincial Office of Primary Education. Subjects were 412 teachers and 731 5th and 6th grade students who were selected by multistage cluster sampling technique. Data were collected by self-administered questionnaires during December 2002-January 2003. Totally 324 teachers (87.6% response rate) and 731 students (100% response rate) answered the questionnaires. Data were then analyzed and presented by using percentage, range and median, and Chi-square test. Study results showed that the teachers perception scores about the importance of substances abuse prevention program in school (importance scores) were high, while their perception scores about the implementation of the program in their schools (implementation scores) were moderate. The difference between these 2 groups of scores wee statistically significant (p<0.05). The importance and implementation scores were high for the risk factor reduction and administrative components of the program, where as those scores for the remedying and data system components were relatively low. Detailed analyses showed that teachers educational level, their previous training about substances abuse, the school characteristics were significantly related to their perception (p<0.05). Importance and implementation scores of the teachers from urban opportunity schools were higher than those score of the teachers from primary schools, particularly the importance score of the administrative, the data system, and that remedying components, and the implementation scores of the administrative component of the program. The students perception scores about the implementation of substances abuse prevention program in their schools were moderate. They perceived that the implementation of promotion and prevention components of the program in their schools were more intense than remedying component, which was in agreement with the teachers perception. Detailed analyses showed the student s gender and GPA, type and size of school were significantly related to students opinion. Teh perception scores of students from urban opportunity schools were higher than those scores of students from primary schools. In conclusion, present study suggests that community participation should be encouraged and substandces abuse training course should be improved in the future development of substances abuse prevention program in schools.